RELATIONSHIPS BETWEEN MORNINGNESS-EVENINGNESS AND PERSONALITY STYLES - Díaz Morales, Juan Francisco; Aparicio García, Marta (Anales de Psicología / Annals of Psychology, 2003)
The purpose of this study is to analyze the personality differential profiles according to circadian type. In a group of 187 people, we have applied the composite scale (CS) of morningness (Smith, Reilly y Midkniff, 1989) which is translated and adapted to the Spanish population by Díaz Ramiro (2000) and the Millon Index of Personality Styles (MIPS) (Millon, 1994), which is translated and adapted to Spanish population (Millon, 2001). The relationship between circadian type and the personality styles have been studied and also the personality profile of each chronotype. The results indicate that the cognitive style used to get and transform the environment information is different between evening- and morning-type individuals. The evening-type subjects prefer the particular information which they set with the previous knowledge. While morning- type subjects prefer the symbolical and ambiguous information. Finally, the evening-type subjects are more doubtful and less condescending with the rest of the people, while the morning-type subjects are more respectful with the social rules.